2021
DOI: 10.1016/j.ceramint.2020.08.284
|View full text |Cite
|
Sign up to set email alerts
|

Zinc substitution effect on the structural, spectroscopic and electrical properties of nanocrystalline MnFe2O4 spinel ferrite

Abstract: This paper reports the structural, morphological, spectroscopic, dielectric, ac conductivity, and impedance properties of nanocrystalline Mn 1-x Zn x Fe 2 O 4 . The nanocrystalline Mn–Zn ferrites were synthesized using a solvent-free combustion reaction method. The structural analysis using X-ray diffraction (XRD) pattern reveals the single-phase of all the samples and the Rietveld refined XRD patterns confirmed the cub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(13 citation statements)
references
References 56 publications
3
10
0
Order By: Relevance
“…At first the increase for sample x = 0.1 (ε′ = 5.89) could be attributed to the incorporation of Zn ions at tetrahedral site that pushes more Fe 3+ towards octahedral site. Thus, hopping mechanism with oxygen vacancy and stress increases which leads to more production of Fe 2+ ions in octahedral sites, which is in accordance with previous reports [ 71 ]. However, a decreasing trend is followed with dopants concentration and strain as well.…”
Section: Resultssupporting
confidence: 92%
“…At first the increase for sample x = 0.1 (ε′ = 5.89) could be attributed to the incorporation of Zn ions at tetrahedral site that pushes more Fe 3+ towards octahedral site. Thus, hopping mechanism with oxygen vacancy and stress increases which leads to more production of Fe 2+ ions in octahedral sites, which is in accordance with previous reports [ 71 ]. However, a decreasing trend is followed with dopants concentration and strain as well.…”
Section: Resultssupporting
confidence: 92%
“…The AC conductivity increases slowly at low frequency but abruptly increases at high frequency. These changes in AC conductivity may occur due to the hopping charge carriers and structure of the grains as well. , It is observed that the conductivity (σ AC ) varies with an increase in frequency. The trapping and fluctuations of conductivity may be due to the increase in temperature of the ceramic samples from the thermal activation energy.…”
Section: Resultsmentioning
confidence: 99%
“…At lower frequencies, the resistive nature of grain boundaries becomes more complicated, resulting in a low conductivity value being observed [ 21 ]. The high conductive structure of grains becomes highly active at higher frequencies, resulting in increased charge carrier hopping between the ions and increased conductivity [ 22 ]. The net conductivity of ceramics can be found using Jonsher’s Power Law (JPL).…”
Section: Resultsmentioning
confidence: 99%